REKONSTRUKSI METODE KRITIK HADIS DENGAN PARADIGMA INTERDISIPLINER - Ulum, Babul (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2022)
The acceptance of the history of heresy na>s}ibi> is a serious problem for the methodology of traditional hadith science. Instead of solving the solution created it adds to the problem because it is ad hoc.  There is a metodogic discretionary or dissimilarity between theory and practice caused by a single paradigm (mono-disciplinary) that makes the study of hadith the way in place. This article offers a new paradigm in approaching hadith, namely the interdisciplinary paradigm as an effort to overcome the stagnation of the methodology of hadith criticism. The problems that arise in hadith science are seen from various points of view; historical, social, and philosophical. As a result, the methodology of the old hadith criticism i.e. the science  of  jarh} wa ta’di>l is subjective cannot be used as the only tool for assessing the quality of hadith. A new approach is needed, namely abductive as a judge for the subjectivity of  traditional jarh} wa ta’di>l clerics.